Efficiency of using SNP markers in the MSTN gene in the selection of the Pushkin breed chickens - N. V. Dementeva; A. B. Vakhrameev; T. A. Larkina; O. V. Mitrofanova (Вавиловский журнал генетики и селекции, 2020)
In the poultry industry, indicators reflecting the growth rate of young stock and the exterior characteristics of chickens are important benchmarks for breeding. Traditional selection based on phenotypic evaluation is characterized by low efficiency with a low character inheritance ratio and is difficult to apply in small groups of animals and birds bred in bioresource collections. The use of molecular genetic markers associated with economically important traits makes it possible to carry out early selection of birds. This entails an increase in the profitability of the poultry industry. Recently, single nucleotide polymorphisms (SNPs) have served as convenient markers for selection purposes. For five generations (P1–P5), an experimental selection of hens of the Pushkin breed was carried out for live weight. It was based on selection for single nucleotide polymorphism rs313744840 in the MSTN gene. As a result, a significant increase in the frequency of allele A in this gene, from 0.11 to 0.50, took place. The association of SNP markers with meat qualities in the experimental group led to changes in the exterior profile of an adult bird at 330 days of age. The individuals with the AA and AG genotypes had the greatest live weight and longest body. As a result of selection, the bird on average became larger due to an increase in the number of heterozygous individuals with long bodies and large chest girths. The depth of the chest and the width of the pelvis increased due to an increase in the frequency of allele A in the experimental population. A tendency towards an increase in these indicators with the substitution of G with A in the genotype was found. Saturation of the population with desirable alleles led to an increase in the average live weight of the chickens. Analysis of the exterior parameters of adult birds showed that this growth is achieved by increasing the depth and volume of the bird body, and not by increasing the length of the limbs. Thus, marker selection carried out for five generations in the experimental population of Pushkin breed chickens to increase body weight has reliably (p < 0.001) changed the exterior profile of adult birds.